Gráﬁco Q-Q modiﬁcado para grandes tamaños de muestra (2015)
The Q-Q plot is a graphical tool for assessing the fit of observed data to a theoretical distribution, in which every single observation in the data is represented by a symbol (usually a dot). In many occasions, due either to natural variations of the data or to a large sample size, the Q-Q plot could be interpreted as a sign of failure of the proposed model. An alternative is to consider a special set of characteristics of the data such as the sample quantiles that, jointly with its theoretical counterparts, allow the user to effectively compare both. We propose and illustrate a modified Q-Q plot that helps to visualise the differences between the observed quantiles and its corresponding theoretical values, and overcome some technical problems of the traditional Q-Q plot.